2007
DOI: 10.4103/0028-3886.33303
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent porphyria presenting with neurological emergency: Review of six cases

Abstract: Acute intermittent porphyria presenting with short duration of gastrointestinal symptoms followed by rapidly progressive fulminant neurological syndrome during first attack is relatively uncommon. It is a neurological emergency and mimics many other psychiatric and medical disorders and can be fatal if it remains undiagnosed and untreated. Further, specific treatment in the form of Heme arginate is not universally available and very costly, so high clinical suspicion and early diagnosis and management of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In a study from the Indian subcontinent, four out of six patients had gastrointestinal symptoms and seizures at the time of presentation. [ 20 ] A descriptive observational study from South Africa reported seizures in five AIP attacks. [ 13 ] Clinical, biochemical, and genetic features of ninety AIP patients were reported in an observational study from the USA.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from the Indian subcontinent, four out of six patients had gastrointestinal symptoms and seizures at the time of presentation. [ 20 ] A descriptive observational study from South Africa reported seizures in five AIP attacks. [ 13 ] Clinical, biochemical, and genetic features of ninety AIP patients were reported in an observational study from the USA.…”
Section: Discussionmentioning
confidence: 99%
“…[192][193][194] Milder acute attacks may settle spontaneously. More severe cases will become protracted and may be complicated by a number of serious problems such as flaccid quadriparesis, 31,182,195,196 seizures, 155,181,[195][196][197] encephalopathy, severe hyponatremia, 139,155,197 and the posterior reversible encephalopathy syndrome. 195,[198][199][200] In our experience, seizures, which are uncommon, are often secondary to factors such as hyponatremia 155,172 and the use of meperidine in high doses.…”
Section: Acute Attackmentioning
confidence: 99%
“…cytochrome P-450) provoke acute deterioration. The emergence of seizures is interpreted by: 1) increased AmLev quantity which blocks GABA receptors, 2) decreased HEM which affects neurotransmitters (triptophan -serotonin), 3) electrolyte disorder due to vomiting (28).…”
Section: Aeds Mechanism Of Action and Prediction Of Adverse Effectsmentioning
confidence: 99%